Determinants Impacting Impulse Buying of Green Beauty Products (Global Journal of Management and Business Research, 2023)
In Bangladesh growing environmental consciousness has caused a substantial shift in the green product market during the past few years Today s consumers are thinking green and are prepared to pay more for ecologically friendly goods Impulse buying is one of the many diverse purchasing habits that consumers have An impulse purchase or buy is any unplanned purchase made by a consumer
Keywords: impulse buying; green beauty products; green perceived value and green trust